Impact of COVID-19 on Economic and Social Indicators of Pakistan: A Comparative Analysis (Journal of Asian Development Studies, 2022)
COVID-19 has acted as a global pandemic resulting in a global lockdown for the many months during 2020. It has impacted inversely on growth rate which declined by -0.38 percent where industry and service sectors are gone through dismissal by representing -2.64 and -0.59 percent passive performance. However agricultural sector has met the growth of 2.67 percent as compare with the last year. The measures government is taking is surely adding more to government expense, the more expense is made in health sector besides offering direct cash support to the nations.  There are liquidity measures taken to secure financial stability. Ehsas monthly program is a big-time challenge for government to pursue, with an allocation of 144 billion which has a cash relief capability for daily wage earners. Till 28 May there is a disbursing of 112.6 billion to almost 9.3 million families. The government simulation packages to large scale manufacturing and 525 basis point cuts in SBP policy rate has caused to regain KSE 100 closed at 16.7 percent in May 2020 that is higher in comparison to March 2020. The government is expecting roll over payment related to power project from China and COVID related support from Asian Development Bank.